The Beginner’s Guide to O-GlcNAc: From Nutrient Sensitive Pathway Regulation to Its Impact on the Immune System - Mannino, Michael P.; Hart, Gerald W. (Frontiers in Immunology, 2022)
The addition of N-acetyl glucosamine (GlcNAc) on the hydroxy group of serine/threonine residues is known as O-GlcNAcylation (OGN). The dynamic cycling of this monosaccharide on and off substrates occurs via O-linked β-N-acetylglucoseamine transferase (OGT) and O-linked β-N-acetylglucoseaminase (OGA) respectively. These enzymes are found ubiquitously in eukaryotes and genetic knock outs of the ogt gene has been found to be lethal in embryonic mice. The substrate scope of these enzymes is vast, over 15,000 proteins across 43 species have been identified with O-GlcNAc. OGN has been known to play a key role in several cellular processes such as: transcription, translation, cell signaling, nutrient sensing, immune cell development and various steps of the cell cycle. However, its dysregulation is present in various diseases: cancer, neurodegenerative diseases, diabetes. O-GlcNAc is heavily involved in cross talk with other post-translational modifications (PTM), such as phosphorylation, acetylation, and ubiquitination, by regulating each other’s cycling enzymes or directly competing addition on the same substrate. This crosstalk between PTMs can affect gene expression, protein localization, and protein stability; therefore, regulating a multitude of cell signaling pathways. In this review the roles of OGN will be discussed. The effect O-GlcNAc exerts over protein-protein interactions, the various forms of crosstalk with other PTMs, and its role as a nutrient sensor will be highlighted. A summary of how these O-GlcNAc driven processes effect the immune system will also be included.